2010
DOI: 10.1111/j.1746-1561.2010.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Get Fit With the Grizzlies: A Community-School-Home Initiative to Fight Childhood Obesity

Abstract: This community-school-home initiative using a professional team's celebrity platform within a certain locale is largely overlooked by school districts and should be considered as a positive strategy to confront childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 8 publications
2
51
0
Order By: Relevance
“…Other scholars have also demonstrated that sport organisations can effectively promote socially beneficial ideas and behaviours, such as support for environmental protection (Inoue and Kent, 2012) and health-related behaviours (Irwin et al, 2010). To date, however, no research has been undertaken to 362 DPM 24,3 test whether and how sport organisations and athletes increase the provision of intangible support from consumers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other scholars have also demonstrated that sport organisations can effectively promote socially beneficial ideas and behaviours, such as support for environmental protection (Inoue and Kent, 2012) and health-related behaviours (Irwin et al, 2010). To date, however, no research has been undertaken to 362 DPM 24,3 test whether and how sport organisations and athletes increase the provision of intangible support from consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Second, scholars have demonstrated that sport has the ability to influence people to support a social cause (Inoue and Kent, 2012;Irwin et al, 2010;Kim and Walker, 2013). Therefore, encouraging the involvement of sport organisations and athletes in disaster relief efforts by clarifying their specific roles may increase public support for disasters and benefit affected people and communities.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of research has begun to investigate the effectiveness of professional sport organizations' CSM initiatives for health promotion (Brady et al 2010;Gray et al 2013a, b;Irwin et al 2010;Pringle et al 2013;Zwolinsky et al 2013). The current study aims to extend this body of research by assessing a CSM initiative using a family-centered approach to improve the health status of the target audience.…”
Section: Introductionmentioning
confidence: 92%
“…It is also imperative to supply sports development with a sufficient number of elite athletes by means of school education and enterprise or social training [32], as sports education institutions can train large numbers of professionals to engage in competitive sports [33]. Apart from this, the industry-academic cooperation [34] model helps integrate students' knowledge and real practices to help bridge the gap between the school curriculum and requirements of the job market. Workplace participation can help enhance the quality and practical experience of professional talents [35], while the implementation of a professional certification system [36] can help guarantee service quality.…”
Section: Expert Human Resourcesmentioning
confidence: 99%
“…[30,31] Formation of industry-academic cooperation (b 3 ) Form cooperative relationships between industries and academia. [32][33][34] …”
Section: Promotion and Assistance Of Government Policy (A)mentioning
confidence: 99%